Pengembangan Aplikasi Simulasi Investasi Reksadana Dengan Algoritma Machine Learning Prophet - Halimah, Siti; Qur’ania, Arie; Anggraeni, Irma; Rama Putra, Gustian (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2024)
Investment is a crucial foundation in financial management that opens opportunities to achieve long-term financial goals. One mutual fund investment platform at a PT is innovating to create a platform tailored to the needs of Generation Z users. However, the platform is currently still under improvement and/or renewal due to functional deficiencies such as the frontend and backend display, as well as the lack of an investment simulation feature that allows investors to predict mutual fund investments. This research focuses on adding an investment simulation feature using a Machine Learning algorithm that can automate the detection of trends and seasonality in mutual fund products. The method used in the website development is the Agile method in the System Development Life Cycle (SDLC). In conducting this research, an analysis of the platform's weaknesses and deficiencies was carried out to compare the website platform to be developed with another platform. Based on the analysis that has been carried out, the development of the platform's functionality and the addition of features were made, namely, updating the latest display on each page and the investment simulation feature. This research uses the PHP programming language and the Laravel framework as well as Firebase as its database. The programming implementation results in a platform that can predict mutual fund product simulations that can be used by investors, thus easily attracting Generation Z to invest in the website platform.